WHODAS 2.0-BO: normative data for the assessment of disability in older adults - Pereira Ferrer, Michele Lacerda; Perracini, Monica Rodrigues; Rebustini, Flavio [UNESP]; Buchalla, Cassia Maria (Revista De Saude Publica, 2019)
OBJECTIVE: To examine the normative data of WHODAS 2.0-BO for older Brazilians (World Health Disability Assessment Schedule - Brazilian version for older people) and its distribution according to sex, age, health, subjective health perception, performance in a mobility test and presence of chronic diseases and depression. METHODS: Cross-sectional study, with 350 participants with 60 years of age or older, men and women, patients of a geriatric specialized center for medical consultations or rehabilitation. The older adults were evaluated using a semi-structured questionnaire containing demographic and clinical data (WHODAS 2.0-BO) and the geriatric depression scale (GDS), having been subsequently subjected to a mobility test (Timed Up and Go). The data were analyzed via their distribution in percentiles of the population and via analysis of variance. RESULTS: Two-hundred and sixty-six (76%) participants were women, and the average age was 71.8 (DP = 6.7) years old. The average score in WHODAS 2.0-BO was 4.3 (DP = 5.2) points, the highest value found having corresponded to 33 points. The average time for the Timed Up and Go test was 10.0 (SD = 3.2) seconds. About 30% of the older adults did not report any difficulties in the tasks evaluated by WHODAS 2.0-BO and half of the sample scored up to two points. CONCLUSIONS: A score corresponding to 12 points in the 90 percentile on a scale from zero to 40 was observed, which suggests severe disability. The score in WHODAS 2.0-BO increased with the advance in age, as well as in the presence of comorbidities, negative health perception, depression, high blood pressure, visual and hearing impairment and mobility impairment.
Keywords: Aged; Disability Evaluation; International Classification of Functioning, Disability and Health; Comorbidity; Socioeconomic Factors; Surveys and Questionnaires, standards